Radio observations of the merging galaxy cluster Abell 520 - Hoang, D.N.; Shimwell, T.W.; Van Weeren, R.J.; Brunetti, G.; Röttgering, H.J.A.; Andrade-Santos, F.; Botteon, A.; Brüggen, M.; Cassano, R.; Drabent, A.; De Gasperin, F.; Hoeft, M.; et al. (EDP SCIENCES S A, 2019)
Context. Extended synchrotron radio sources are often observed in merging galaxy clusters. Studies of the extended emission help us to understand the mechanisms in which the radio emitting particles gain their relativistic energies. Aims. We examine the possible acceleration mechanisms of the relativistic particles that are responsible for the extended radio emission in the merging galaxy cluster Abell 520. Methods. We performed new 145 MHz observations with the LOw Frequency ARay (LOFAR) and combined these with archival Giant Metrewave Radio Telescope (GMRT) 323 MHz and Very Large Array (VLA) 1.5 GHz data to study the morphological and spectral properties of extended cluster emission. The observational properties are discussed in the framework of particle acceleration models associated with cluster merger turbulence and shocks. Results. In Abell 520, we confirm the presence of extended (760 × 950 kpc 2 ) synchrotron radio emission that has been classified as a radio halo. The comparison between the radio and X-ray brightness suggests that the halo might originate in a cocoon rather than from the central X-ray bright regions of the cluster. The halo spectrum is roughly uniform on the scale of 66 kpc. There is a hint of spectral steepening from the SW edge towards the cluster centre. Assuming diffusive shock acceleration (DSA), the radio data are suggestive of a shock Mach number of SW = 2.6-0.2 +0.3 that is consistent with the X-ray derived estimates. This is in agreement with the scenario in which relativistic electrons in the SW radio edge gain their energies at the shock front via acceleration of either thermal or fossil electrons. We do not detect extended radio emission ahead of the SW shock that is predicted if the emission is the result of adiabatic compression. An X-ray surface brightness discontinuity is detected towards the NE region that may be a counter shock of Mach number NE X = 1.52±0.05. This is lower than the value predicted from the radio emission which, assuming DSA, is consistent with NE = 2.1 ± 0.2. Conclusions. Our observations indicate that the radio emission in the SW of Abell 520 is likely effected by the prominent X-ray detected shock in which radio emitting particles are (re-)accelerated through the Fermi-I mechanism. The NE X-ray discontinuity that is approximately collocated with an edge in the radio emission hints at the presence of a counter shock.